The effect of green intellectual capital on organizational reputation - Youssef Muhammad, Akram; Hussein Shiaa, Hossam (Iraqi Journal for Administrative Sciences, 2024)
The research reviews the understanding of the impact of green intellectual capital on organizational reputation by analyzing the relationship between their dimensions. It aims to assist the management of private universities and colleges in enhancing sustainable environmental performance. The study began with a main problem that included questions about the nature of the relationship between its variables, including the extent of interest of private universities in Karbala in green intellectual capital and its dimensions. The study adopted purposive sampling, with the number of individuals who responded to the study being 131 leaders and academics. The researchers utilized various statistical methods such as SPSS, Microsoft Excel 2016, and AMOS. The results showed significant correlation and influence between green intellectual capital and organizational reputation. The researchers recommend increasing focus on green intellectual capital dimensions to improve organizational reputation.